PENERAPAN PREZI DEKSTOP SEBAGAI MEDIA PRESENTASI UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 9 PEKANBARU - Dzulhijjah, Putri Dzulhijjah; Noer, Asmadi M. Noer; Linda, Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research aims to increase student learning achievement on the topic of hydrocarbons in class X Senior High School (SMAN) 9 Pekanbaru. Prezi Dekstop is used when the teacher explains the topic being able to explain abstact concepts into concrete, one of them on the topic of hydrocarbons. The research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of class X4 as the experimental class and students of class X2 as th Kata Kunci:Prestasi Belajar, Prezi Dekstop, Hidrokarbon